PREVALENCE OF OSTEOPOROSIS AND ITS ASSOCIATED FACTORS AMONG OUTPATIENTS AT THAI NGUYEN UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
The objective of this study was to investigate the prevalence of osteoporosis and analyze related factors in outpatients at the University of Medicine and Pharmacy Hospital of Thai Nguyen. A cross-sectional descriptive study was conducted on 72 patients aged ≥40 years. Bone mineral density was assessed using dual-energy X-ray absorptiometry (DXA) at the lumbar spine and femoral neck, and data were analyzed with SPSS version 25.0. The overall prevalence of osteoporosis was 23.6%, including 18% at the lumbar spine and 9.9% at the femoral neck. The prevalence increased with age and was higher in females (31.3%) compared to males (4.3%). Statistical analysis showed significant associations between osteoporosis and age, sex, and hypertension (p < 0.05), whereas BMI, occupation, and diabetes were not significantly related. These findings highlight that osteoporosis is a common health issue among outpatients, particularly in older women and patients with hypertension, emphasizing the importance of early screening and preventive interventions to reduce the risk of fractures and the associated disease burden.
Keywords: Osteoporosis, DXA, Thai Nguyen